Fast switching negative dielectric anisotropic multicomponent mixtures for vertically aligned liquid crystal displays. (24th April 2015) - Dasgupta, P; Das, M K; Das, B
Abstract: Negative dielectric anisotropic nematic multicomponent mixtures are particularly attractive in vertically aligned mode liquid crystal displays for achieving faster response time. In this work, we report the mesomorphic and physical properties (e.g. birefringence, dielectric anisotropy, bend elastic constant, relaxation time and rotational viscosity) of three nematic multicomponent mixtures based solely on laterally fluorinated aromatic rigid core structures. A nine component Base mixture was prepared and further modified into two different ten component mixtures using suitable laterlally fluorinated tolane dopants. These mixtures exhibit reasonably large values of dielectric anisotropy, low values of rotational viscosity as well as a high figure of merit which is desirable for reducing the device response time. The mixtures emerged to be promising candidate for their applicability in vertically aligned mode display devices.